2021
DOI: 10.1093/ehjopen/oeab047
|View full text |Cite
|
Sign up to set email alerts
|

Resources for cardiovascular healthcare associated with 30-day mortality in acute myocardial infarction with cardiogenic shock

Abstract: Background Although primary percutaneous coronary intervention (PCI) and mechanical circulatory support (MCS), such as extracorporeal membrane oxygenation (ECMO) or intra-aortic balloon pumping (IABP), have been widely used for acute myocardial infarction patients with cardiogenic shock (AMICS), their in-hospital mortality remains high. This study aimed to investigate the association of cardiovascular healthcare resources with 30-day mortality in AMICS. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 30 publications
1
4
0
Order By: Relevance
“…This might be because COVID-19 directly impacts on coronary circulation and/or myocardial injury causing an increase in mortality. 3 Additionally, in our study, although the proportion of patients treated with PCI in the before COVID-19 pandemic group was similar to those in previous reports that extracted data from the JROAD DPC, 19 the proportion in the COVID-19-positive group was low compared with the before COVID-19 pandemic group. Thus, the decrease in the proportion of patients treated with PCI might also be one of the reasons for the higher mortality in the COVID-19-positive group.…”
Section: Mortality Of Ami During the Covid-19 Pandemicsupporting
confidence: 88%
“…This might be because COVID-19 directly impacts on coronary circulation and/or myocardial injury causing an increase in mortality. 3 Additionally, in our study, although the proportion of patients treated with PCI in the before COVID-19 pandemic group was similar to those in previous reports that extracted data from the JROAD DPC, 19 the proportion in the COVID-19-positive group was low compared with the before COVID-19 pandemic group. Thus, the decrease in the proportion of patients treated with PCI might also be one of the reasons for the higher mortality in the COVID-19-positive group.…”
Section: Mortality Of Ami During the Covid-19 Pandemicsupporting
confidence: 88%
“…Previous studies using JROAD‐DPC data reported a ratio of male to female AMI patients of about 7 to 3 7,8 . On the other hand, our study population was 89.3% male.…”
Section: Discussionmentioning
confidence: 52%
“…Previous studies using JROAD-DPC data reported a ratio of male to female AMI patients of about 7 to 3. 7,8 On the other hand, our study population was 89.3% male. In contrast to these other studies investigating AMI patients of all ages, our study investigated AMI patients between 0 and 60 years old because KD was first reported in Japan in 1967 and diagnosed while patients were infants or young | 1177 children.…”
Section: Discussionmentioning
confidence: 83%
“…The present study was a retrospective observational study based on a nationwide Japanese administrative case-mix Diagnostic Procedure Combination (DPC) database, the Japanese Registry Of All cardiac and vascular Disease (JROAD)-DPC. [4][5][6] In brief, the JROAD-DPC database is DPC-based payment health insurance claim data about hospitalization due to cardiovascular diseases collected…”
Section: Study Protocol and Populationmentioning
confidence: 99%
“…The remaining participants were divided into AMI-CS and AMI-NCS groups based on their condition at admission. 5 The AMI-CS, equivalent to the SCAI C/D/E group, was defined as Killip classification 3 or 4 that met at least one of the following criteria: (1) mechanical circulatory support use; or (2) intravenous administration of catecholamines on admission. Patients with Killip classification 3 (n=9,598) and 4 (n=6,691), or out-of-hospital cardiac arrest (n=484) were also excluded for the possibility of CS.…”
mentioning
confidence: 99%